Mathematical modelling of the role of mucosal vaccine on the within-host dynamics of Chlamydia trachomatis. (21st July 2020) - Akinlotan, Morenikeji Deborah; Mallet, Dann G.; Araujo, Robyn P.
Highlights: We propose and thoroughly analyse a detailed eight-species model of the in-host interactions between Chlamydia trachomatis infection, the immune system, and a mucosal vaccine. Our modelling framework provides biologists and clinicians with a new level of insight into the relationship between requisite vaccine efficacy and a number of key properties of the immune system. Our results suggest that the minimum vaccine efficacy required to promote a stable Chlamydia -free state in vivo is likely to be on the order of 86%, based on the best available estimates of immune system parameters reported in the literature. Our analysis reveals that minimum vaccine efficacy is influenced by several key characteristics of the immune system, which could vary from individual to individual. Abstract: A mathematical model of the within-host replicative dynamics of C. trachomatis infection and its interactions with the immune system, in the presence of a mucosal vaccine, is presented. Our aim is to estimate the requisite efficacy of an efficacious mucosal vaccine that could promote a stable disease-free state in vivo . Sensitivity analysis was used to quantify how variability in the model parameters influence the value of the disease threshold R 0 . This shows that the two most important factors to be considered for achieving a disease-free state state in vivo, based on their influence on R 0, are the efficacy of the Chlamydia vaccine, and the rate at which the humoral immune response protects healthy epithelial cells from infection. Numerical simulations of the model show that a vaccine with a minimum efficacy of 86% may be required for the in vivo control of Chlamydia burden. Such effective but imperfect Chlamydia vaccine could confer long-term protective immunity to genital Chlamydia infections. Conditions under which lower vaccine efficacies may suffice are also explored.